A Malay language-based visual programming language for personal digital assistant - Sulaiman, Md. Nasir; Anuar, Sazly; Muda, Zaiton; Ibrahim, Hamidah; Mustapha, Aida (2008)
Most of the visual programming languages that have been developed so far do not focus on Personal Digital Assistant (PDA), due to the limited screen size and resources. This paper proposes the Malay language-based Visual Programming Language (MaVi) on PDA. The syntax and the semantics of MaVi are grammatically designed based on the visual programming. The hierarchical layout technique is used to optimize the graph produced, so that it can suit on limited size of the PDA screen. The grammar of the developed language is a subset to a Java language, but it is in a graphical representation. The compilation of the program will produce a byte code, which can be executed in any PDAs that has a Java Virtual Machine (JVM). The testing on different test programming is carried out to prove that it can be executed on embedded devices and produces expected output.